The Practice Of Helping As A Form Of Social Alms In Tunggul Pawenang Village, Pringsewu, Indonesia - Afani Adam, Muhammad; Eka Putri, Sheilla Aulia (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This research aims to identify and analyze the practice of helping as a form of social alms in Tunggul Pawenang Village, Pringsewu. In this context, helping is not only about physical assistance, but also includes social, economic, and cultural aspects of the community. Methodology: The method used is a qualitative approach with interview, observation, and documentation techniques. Findings: The results show that despite significant economic differences among residents, the spirit of cooperation is maintained through contributions in the form of labor, goods, and money. Participation in social activities is influenced by an individual's economic capacity, with those who are better off contributing more in the form of materials, while those who are less well-off participate more actively in the form of labor and work. The role of the village head and community leaders is crucial in organizing and motivating the community to maintain the spirit of gotong royong. This research provides new insights into the importance of social roles in building community solidarity, especially in the face of existing social inequalities.